Edukasi William Flexion Exercise sebagai Upaya Peningkatan Pengetahuan dan Pencegahan Low Back Pain pada Drivers Mobil Online di Kota Malang - Rosidatussholikhah Rosidatussholikhah; Nungki Marlian (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
A safe and healthy environment is crucial to minimizing accidents and occupational diseases, and this is where Occupational Health and Safety (OHS) comes in. Workers in the informal sector, such as online drivers, are more likely to experience musculoskeletal problems, especially low back pain (LBP), because they frequently lack proper occupational protection and health services. LBP is a complaint of lower back pain that can be brought on by extended periods of static sitting, bad posture, and personal characteristics like body mass index, smoking, and length of service. The purpose of this program is to educate online drivers in Malang City, East Java, and help them avoid LBP. The risk of LBP can be decreased in part by promoting physical activity and education. One recommended intervention is the William Flexion Exercise (WFE), an exercise aimed at improving posture, increasing muscle strength and flexibility, and reducing lower back pain. Implementing WFE education and training for online car drivers is anticipated to strengthen OHS awareness and reduce the incidence of LBP among informal sector workers.